On a Method for Determining Age of Trees without Annual Rings - Pande, D. C. (Indian Forester, 1960)
A computational method for determining the age of trees without annual rings was proposed in III Silvicultural Conference and incorporated in the Tree & Crop Measurement Manual. This method fails for higher diameter classes and does not give consistent values. A new method is deduced from theoretical considerations and a general formula derived which gives fairly acceptable estimates over a wide range of diameters.